Enhancing MSMEs Business Governance within the Baduy Indigenous Community - Gilang Fahreza; Dyah Mustika Wardani; Nova Yudha Adriansyah Putra; Lilik Edi Saputro (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
The Outer Baduy are an indigenous community that is more open to external cultural influences than the Inner Baduy and have gradually adopted modern technology to support their economic activities. Observations indicate that most micro, small, and medium enterprises (MSMEs) in the community already have social media accounts and actively use digital devices. However, these platforms have not been utilized optimally for product promotion and business development. Many business owners reported feeling embarrassed or lacking confidence to appear in promotional content, limiting the effectiveness of their digital marketing efforts. This community service activity aimed to improve digital marketing capabilities by providing training on the use of social media and marketplace platforms, as well as developing content strategies that remain consistent with local cultural values. The program also encouraged participants to understand the importance of branding and customer engagement in the digital marketplace. The results suggest that continued mentoring addressing both technical skills and psychological barriers is essential to build self-confidence, strengthen digital literacy, and foster sustainable digital marketing practices. A personalized, culture-based approach is therefore crucial for increasing the active participation and competitiveness of Outer Baduy MSMEs in the digital economy.